Research on Cold Core Eddy Change and Phytoplankton Bloom Induced by Typhoons: Case Studies in the South China Sea - Xiao-dong Shang; Hai-bin Zhu; Gui-ying Chen; Chi Xu; Qi Yang (Advances in Meteorology)
The effects of 8 typhoons which passed by coldcore eddy (CCE) areas in the South China Sea (SCS) from 1997 to 2009 were observed and evaluated. The changes in the preexisting CCE acted upon by typhoons were described by eddy kinetic energy (EKE) and eddy available gravitational potential energy (EAGPE). The mechanical energy of CCE was estimated from a two-layer reduced gravity model. Comparing with the scenario that typhoon passes by the region without CCEs, the preexisting CCE area plays an important role in the increase of chlorophyll-a (chl-a) concentration in the CCEs impacted by the typhoons. The preexisting chl-a in CCE is about 25%~45% (8%~25%) of postexisting chl-a in CCE for higher (slower) transit speed typhoons. If the EAGPE of CCE increases greatly after typhoon passing by with slow transit speed, so does the chl-a in the CCE area. The EKE (EAGPE) changes of the preexisting CCE are in the order of O(1014~1015 J). EKE and EAGPE of CCE are dominantly enhanced by typhoon with slow transit speed (<3 m/s) and the posttyphoon EAGPE is always larger than posttyphoon EKE for 8 cases. The maximum EAGPE change of the preexisting CCE reaches 5.11×1015 J, which was induced by typhoon Hagibis.